Dinamika Persepsi Pelaku UMKM terhadap Dampak Perang Dagang Amerika Serikat–Tiongkok di Bangka - Ulfa; Anggita, Wenni; Huda, Syamsul (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
The trade war between the United States and China, which took place from 2018 to 2020, triggered dynamics in global trade and affected the economies of partner countries, including Indonesia. This study aims to explore the perceptions of Micro, Small, and Medium Enterprises (MSMEs) in the Bangka Belitung Islands Province regarding the impact of the trade conflict. The research method used is qualitative with a case study approach, involving in-depth interviews with several MSME actors in the Bangka region. Using a qualitative approach with semi-structured interview techniques involving 80 MSME actors in Bangka, this study found that most MSMEs experienced indirect impacts such as rising raw material prices and declining revenues. However, they had limited understanding of how these were linked to the global trade war. This study highlights the importance of improving international economic literacy and implementing adaptive policies that support the sustainability of local MSMEs. The findings show that MSME perceptions vary, ranging from concerns over rising raw material costs and supply chain disruptions to opportunities for market expansion due to shifting trade patterns. The study also found that the level of adaptation among MSMEs to the trade war conditions was influenced by access to information, resource capacity, and existing business networks. These findings provide important insights for policymakers in formulating support strategies to.
Keywords: MSMEs; Bangka Belitung; Trade War; Business Actors’ Perceptions; Global economy